Simulation of mechanical heart valve dysfunction and the non-newtonian blood model approach - Chen, Aolin; Basri, Adi Azriff; Ismail, Norzian; Tamagawa, Masaaki; Zhu, Di; Ahmad, Kamarul Arifin (Hindawi Publishing, 2022)
The mechanical heart valve (MHV) is commonly used for the treatment of cardiovascular diseases. Nonphysiological hemodynamic in the MHV may cause hemolysis, platelet activation, and an increased risk of thromboembolism. Thromboembolism may cause severe complications and valve dysfunction. This paper thoroughly reviewed the simulation of physical quantities (velocity distribution, vortex formation, and shear stress) in healthy and dysfunctional MHV and reviewed the non-Newtonian blood flow characteristics in MHV. In the MHV numerical study, the dysfunction will affect the simulation results, increase the pressure gradient and shear stress, and change the blood flow patterns, increasing the risks of hemolysis and platelet activation. The blood flow passes downstream and has obvious recirculation and stagnation region with the increased dysfunction severity. Due to the complex structure of the MHV, the non-Newtonian shear-thinning viscosity blood characteristics become apparent in MHV simulations. The comparative study between Newtonian and non-Newtonian always shows the difference. The shear-thinning blood viscosity model is the basics to build the blood, also the blood exhibiting viscoelastic properties. More details are needed to establish a complete and more realistic simulation.